Direitos fundamentais e o não-confisco tributário - Franco Neto, Georgenor de Sousa (2009)
This research analyzes some relation among the principle of bar the tax with confiscation effect and the fundamental rights. The theoretic base is the semantic-logic constructivism, with influence from the constitutional concretion. With the distinction between normative text (provision) and norm (interpretation), using the deontic logic to comprehensive the rule of law s structure. Next, analyze fundamental rights, fix a concept and some distinct s notes related the human rights. We support it in Discursive Theory and expose the way to apply them through proportionality s standard. With base in the history s preceding, we determination the fundamental rights related non-confiscation with the property right, professional and commercial activity freedoms and vital minimum. We continuing exposing the relationship between State s obligation and the pay to owe. After a panoramic of doctrine, we analyze the incidence of non-confiscation principle in each tax and its relation with tax capacity. In the end, expose the connection among fundamental rights and the principle of prohibit of the confiscation and in each sphere of power (Legislative, Executive and Judiciary). Concluding, we mark the existential of big variation in the way how the confiscation is analyze depends what is de branch talk about. We notice too, that the violation at that principle only could be encounter by means of reference at the fundamental rights, always thought the disrespect of the property right